Myco-Biocontrol of Insect Pests: Factors Involved, Mechanism, and Regulation. (23rd February 2012) - Sandhu, Sardul Singh; Sharma, Anil K.; Beniwal, Vikas; Goel, Gunjan; Batra, Priya; Kumar, Anil; Jaglan, Sundeep; Sharma, A. K.; Malhotra, Sonal
Abstract : The growing demand for reducing chemical inputs in agriculture and increased resistance to insecticides have provided great impetus to the development of alternative forms of insect-pest control. Myco-biocontrol offers an attractive alternative to the use of chemical pesticides. Myco-biocontrol agents are naturally occurring organisms which are perceived as less damaging to the environment. Their mode of action appears little complex which makes it highly unlikely that resistance could be developed to a biopesticide. Past research has shown some promise of the use of fungi as a selective pesticide. The current paper updates us about the recent progress in the field of myco-biocontrol of insect pests and their possible mechanism of action to further enhance our understanding about the biological control of insect pests.